Not All Juices are the Same: The Superior Perception of and Preference for Florida Orange Juice. (23rd November 2022) - Heng, Yan; Yoon, Sungeun; House, Lisa; Gao, Zhifeng
Abstract: The Florida orange juice industry has experienced great challenges—declining orange juice consumption and a domestic supply shortage that has led to increasing imports over the past decade. As growers look for a foothold, the question remains whether it is better to continue promoting orange juice (OJ) sales by focusing on the Florida "brand" or whether orange juice, in general, should be promoted using a federal marketing program. This study aims to identify the value of promoting "Florida" on OJ products to help the industry understand the potential benefits of enhancing the image of "Florida" in consumers' perceptions of OJ.